2013
DOI: 10.4278/ajhp.120213-qual-87
|View full text |Cite
|
Sign up to set email alerts
|

Is Usage of a Wellness Center Associated with Improved Quality of Life?

Abstract: In a large sample of employees, use of a wellness center during a 12-month period was associated with benefits for physical QOL. QOL is an important domain of wellness; therefore, in addition to measuring physiologic changes, examining potential QOL changes may be another important outcome measure for wellness centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…6 Wellness coaching has also been found to improve physical activity level 7 and effectively treat weight management. 8 More recently, Mettler and colleagues 9 found that participation in wellness coaching improved motivation, importance, and confidence for making positive health behavior change in such areas as life satisfaction, energy level, healthy weight, physical activity, nutrition, managing health, and mental fitness. Clearly, more outcome studies are warranted, given the increasing prevalence of wellness coaching in our country.…”
mentioning
confidence: 98%
“…6 Wellness coaching has also been found to improve physical activity level 7 and effectively treat weight management. 8 More recently, Mettler and colleagues 9 found that participation in wellness coaching improved motivation, importance, and confidence for making positive health behavior change in such areas as life satisfaction, energy level, healthy weight, physical activity, nutrition, managing health, and mental fitness. Clearly, more outcome studies are warranted, given the increasing prevalence of wellness coaching in our country.…”
mentioning
confidence: 98%
“…5 This would empower them to take greater omphalic role in self-care, knowing their numbers and treatment adherence, which could be bolstered with training and support to achieve sustainability. The returns on this investment are humongous with regards to patient satisfaction and quintessentially improved health outcomes 9,10 ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…4 The overall functioning and existence of the clinic incorporating the wellness initiatives is bestowing healthy lifestyles and behavioural modification among the associates. 5 The services of wellness clinics helped in transforming the knowledge, attitude and practice of the medical conditions among the associates. 5,6 It was supported by the doctors and paramedics by placing greater emphasis on preventive aspect of healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were concerned that if they failed to achieve their health goal their monthly health insurance premium would return to the standard non-discounted rate plus a $50 reentry fee. In general, participants' feelings of embarrassment, shame, and frustration were not aligned with more holistic definitions of wellness (Clark et al, 2013;Dale, Smith, Chess, & Norlin, 2006).…”
Section: Discussionmentioning
confidence: 99%